The Determination of Antioxidant Vitamin Levels, Radical Scavenging Effect of Elaeagnus Angustifolia Methanol Extracts Against to MDA - Yıldırım, Işıl; Gökçe, Zehra (Hacettepe Üniversitesi, 2014)
Free radical; atomic or molecular structures with single-electron compounds. With other molecules that can be very easy to electron exchange across the molecules “an oxidant molecules” or “reactive oxygen partic- les” also be said. Antioxidants compound that stop the formation of the free radicals or dispel negative effects of items. this, to do inhibited the radical reaction systems. or non-toxic products there is no turning it on. The most of antioxidants found in foods. With an antioxidant-rich diet, free radicals and active oxygen consisting of the which is the basis of disease oxidative damage can be prevented [1]. This the nutrition-type especially fruits vegetables natural anti-oxidant resources [2]. In this study aimed that to determine the Antioxidant vitamin levels, radical-scavenging properties of Elaeagnus angustifolia methanol extracts against to prevent formation MDA. The material obtained from a plant seller in Elazığ. Extracted from plants was performed using methanol solvent. Extraction process was done of plant parts by weight of 2 grams in weight was 10 times the solvents. Spectral analysis with Shimadzu model UV 1400 spectrophotometer, antioxidant vitamins with the same brand HPLC was carried out. Plant extracts of the DPPH radical knockdown activity the method specified,[3] the OH- radical destruction the method indicated[4], Antioxidant capacity ABTS radical destruction activity[5] lipid peroxidation LPO measurements using as standard Fenton Quercetin, Resvesterol reagents MDA-TBARS by the method[6], vitamins analysis using the methods [7, 8, 9] was performed. Radical scavenging activity from 100?L-800?L concentration measurements were performed with two evil-fold increase. Results of DPPH radi- cal scavenging and OH· radical knock down activity increased with concentration difference. MDA analysis com- parison with the control group showed significant differences. MDA analysis with controls Quercetin standards compared were not statistical different, both the extracted measurements and control groups fenton reagent and resveratrol standard compared with a significant statistical difference was observed. p